2015
DOI: 10.1021/sc500840b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Performance of Hollow Spherical Sludge Carbon Prepared from Sewage Sludge and Polystyrene Foam Wastes

Abstract: Although sludge carbons have been widely studied, no attention has been paid to the preparation and application of hollow sludge carbon. In this study, innovative hollow spherical sludge carbons (HSCs) were prepared by pyrolyzing polystyrene foam sphere @sludge. The precursors, including sewage sludge and polystyrene foam, are solid wastes and produced in large volumes around the world. By this method, HSCs with a tunable shell thickness from 0.2 to 2.5 mm were obtained. The batch and column experiments show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…However, there are challenges in effectively cleaning up pollutants. First, the pollutants are typically removed by absorption or skimming and then disposed of . Accordingly, this results in not only secondary contamination, but also leads to the absorbent material and pollutant not being recovered in an economical and useful manner.…”
mentioning
confidence: 99%
“…However, there are challenges in effectively cleaning up pollutants. First, the pollutants are typically removed by absorption or skimming and then disposed of . Accordingly, this results in not only secondary contamination, but also leads to the absorbent material and pollutant not being recovered in an economical and useful manner.…”
mentioning
confidence: 99%
“…Hollow spherical sludge carbons were prepared by Wu et al . from polystyrene foam sphere and sludge pyrolysis, which was then employed as an adsorbent to treat wastewater . Conversion of waste expanded polystyrene into polymeric azo dyes with sulphonamide group was accomplished by Liu et al .…”
Section: Plastic Waste Management: Current State and Conventional Metmentioning
confidence: 99%
“…66 Hollow spherical sludge carbons were prepared by Wu et al from polystyrene foam sphere and sludge pyrolysis, which was then employed as an adsorbent to treat wastewater. 67 Conversion of waste expanded polystyrene into polymeric azo dyes with sulphonamide group was accomplished by Liu et al through chlorosulfonation, amidation, hydrolysis, diazotization and coupling reactions. 68 Liao et al reported the preparation of doped carbon catalyst for the reduction of oxygen employing precursors; polystyrene foam, melamine and iron chloride.…”
Section: Other Valorizing Optionsmentioning
confidence: 99%
“…Recently, research has been focused particularly on transforming sewage sludge into porous carbon materials as adsorbents. Such types of adsorbents or carriers have a particular ability to remove heavy metals, dyes, polycyclic aromatic hydrocarbons, antidepressants, gases, etc . From the point of view of sludge recycling, high‐temperature carbonization of sewage sludge for producing porous carbon materials is considered as one of the most attractive methods .…”
Section: Introductionmentioning
confidence: 99%